Service Quality and Clients Satisfaction of Digital Dental Diagnostics in Highly Urbanized Cities in Western Visayas - Mendez, Paul Brian S.; Salugsugan, John Clifford (Philippine Social Science Journal, 2025)
Utilizing a descriptive correlational design with 270 randomly selected participants in Bacolod and Iloilo, this study assessed the service quality of digital dental diagnostics and its relationship with client satisfaction. The findings revealed very high service quality ratings—particularly in empathy and responsiveness—which strongly correlated with high client satisfaction, though demographic nuances existed: younger clients prioritized responsiveness, while older clients valued assurance. These results validate the importance of client-centered care in digital dentistry and suggest that providers should focus on robust quality assurance and staff training to maintain these standards. Future research should extend these findings through longitudinal designs and structural equation modeling to evaluate the evolving impact of emerging technologies, such as AI, on the patient experience.